2009
DOI: 10.1002/jcb.22129
|View full text |Cite
|
Sign up to set email alerts
|

N‐terminal residues of the yeast pheromone receptor, Ste2p, mediate mating events independently of G1‐arrest signaling

Abstract: In Saccharomyces cerevisiae, mechanisms modulating the mating steps following cell cycle arrest are not well characterized. However, the N-terminal domain of Ste2p, a G protein-coupled pheromone receptor, was recently proposed to mediate events at this level. Toward deciphering receptor mechanisms associated with this mating functionality, scanning mutagenesis of targeted regions of the N-terminal domain has been completed. Characterization of ste2 yeast overexpressing Ste2p variants indicated that residues Il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…Haploid cells locate mating partners by polarizing their growth in the direction of the highest pheromone concentration [11,12]. Mutations in either pheromones or receptors can alter mating efficiency [13][14][15], and pheromone-receptor specificity has been proposed as a possible mechanism for mate discrimination between those species whose pheromone peptide sequences differ [3,16]. Attraction to pheromones produced by incompatible partners is particularly costly for yeast because each cell can mate only once; zygote inviability or sterility is equivalent to death for the mating haploids.…”
Section: Resultsmentioning
confidence: 99%
“…Haploid cells locate mating partners by polarizing their growth in the direction of the highest pheromone concentration [11,12]. Mutations in either pheromones or receptors can alter mating efficiency [13][14][15], and pheromone-receptor specificity has been proposed as a possible mechanism for mate discrimination between those species whose pheromone peptide sequences differ [3,16]. Attraction to pheromones produced by incompatible partners is particularly costly for yeast because each cell can mate only once; zygote inviability or sterility is equivalent to death for the mating haploids.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the Ste2p mutantsY266C, Q149R and W295C exhibited robust FUS1-lacZ activity, but little to no growth arrest activity [43] [65] [66]. Similarly, a divergence in correlation between mating efficiency and FUS1-lacZ induction has been reported for I24C and I29 mutants which exhibited approximately 50% and 100% of the WT FUS1-lacZ activities, respectively, but only <0.09% and 4.6% of the WT mating efficiency[29]. Mutations of receptors resulting in biased activation of specific signaling pathways has been described for other GPCRs [6770].…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminus of Ste2p is ~48 amino acids long, and it harbors two glycosylation sites (N25 and N32) which were eliminated by mutation (N25A and N32A) without affecting receptor function [25]. Other studies indicated that the N-terminus contributed to receptor dimerization [26, 27], and three residues (Pro 15, Ile24, and Ile29) were found to be essential for mating but not for signaling as measured by growth arrest and reporter gene ( FUS1 ) activation assays [28, 29]. Truncation of parts of the N-terminus implicated this domain in cellular fusion (mating) during late stages of conjugation of opposite mating types [29].…”
Section: Introductionmentioning
confidence: 99%
“…Towards validating reported alternate functionalities of Ste2p (10,12,14,16,18) according to current standards (6), a relative mutational-derived bias method was applied. This method accounts for systemic and observational bias that makes direct comparison of data between assays otherwise impossible.…”
Section: Discussionmentioning
confidence: 99%
“…Some examples of these include mutations I24C and I29C in the N-terminus, yielding a phenotype that has strong G-protein-dependent MAPK signalling and cell cycle arrest activity, but no actual mating functionality (18). Similarly, mutation S251L, in the central region of transmembrane (TM) 6, also yielded normal signalling, but a weak-mating phenotype (19) (Fig.…”
mentioning
confidence: 99%